Численное исследование сжигания резервного топлива в топке котла БКЗ-210-140 - Гиль А. В. Андрей Владимирович; Заворин А. С. Александр Сергеевич; Лебедь Д. В. Дмитрий Викторович; Старченко А. В. Александр Васильевич (2014, 2014)
Заглавие с титульного листа